Coping with complex environments: the case of digital healthcare technology producers - Macnaughtan, Lorena (2019)
The aim of this thesis is to enrich the understanding of institutional complexity. To that end, my research focuses on an emergent field, as the most acute instantiation of institutional complexity, in addition to being an understudied phenomenon. Theoretically, the approach is anchored in the institutional logics perspective and the concept of institutional work. My research design is an inductive multi-level, multi-case study, found adequate to investigate a poorly understood and complex phenomenon. The research setting is the emerging field of digital health, at the intersection of healthcare and consumer digital technologies fields.